Curious George's ABCs - Rey, H. A. (Hans Augusto), 1898-1977 (Boston, Mass. : Houghton Mifflin, 1998)
Curious George watches and participates as the letters of the alphabet are illustrated with common associated objects.
Cover title.
On board pages.
Keywords: English language -- Alphabet -- Juvenile literature; Monkeys -- Juvenile fiction; Monkeys -- Fiction; Alphabet -- Fiction; Toy and movable books